(untitled) (Health Renaissance, 2017)
Background: Hypertension is a common disease affecting about 20% of the adult population, both in developed and developing world (WHO 2002). It is one of the serious public health problems. Timely detection, compliance with lifestyle modification and use of drugs are important for effective management of this condition. Objective: To find out the prevalence of systemic hypertension in the general outpatient department and to study the effect of drugs and lifestyle education on the blood pressure over time. Methods: This was an interventional series of cases involving diagnosis and management of patients with BP higher than 140/90 or with known hypertension. All the subjects included were given life style education to see the effect of change of life style on blood pressure over time. Results: A total of 258 subjects were screened and 145 (56%) were diagnosed as hypertensive. Of the total, 75 (29%) had a blood pressure level in pre- hypertensive range. Whereas, 42 (16.3%) had hypertension of stage 1, and 28 (11%) had hypertension of stage 2. Forty- nine patients came for first follow up, 40 patients for second and 10 patients for the third follow up. Blood pressure started to decrease with second follow up. Conclusion: This study demonstrated that the prevalence of hypertension is 56% in the general outpatient department. The lifestyle education can have positive impact on blood pressure control. Health Renaissance 2015;13 (1): 58-67